PI3K/Akt pathway restricts epithelial adhesion of Dr+Escherichia coli by down-regulating the expression of decay accelerating factor. (May 2014) - Banadakoppa, Manu; Goluszko, Pawel; Liebenthal, Daniel; Nowicki, Bogdan J; Nowicki, Stella; Yallampalli, Chandra
The urogenital microbial infection in pregnancy is an important cause of maternal and neonatal morbidity and mortality. Uropathogenic Escherichia coli strains which express Dr fimbriae (Dr+) are associated with unique gestational virulence and they utilize cell surface decay accelerating factor (DAF or CD55) as one of the cellular receptor before invading the epithelial cells. Previous studies in our laboratory established that nitric oxide reduces the rate of E. coli invasion by delocalizing the DAF protein from cell surface lipid rafts and down-regulating its expression. The phosphoinositide 3-kinase/protein kinase B (PI3K/Akt) cell signal pathway plays an important role in host-microbe interaction because many bacteria including E. coli activate this pathway in order to establish infection. In the present study, we showed that the PI3K/Akt pathway negatively regulated the expression of DAF on the epithelial cell surface and thus inhibited the adhesion of Dr + E. coli to epithelial cells. Initially, using two human cell lines Ishikawa and HeLa which differ in constitutive activity of PI3K/Akt, we showed that DAF levels were associated with the PI3K/Akt pathway. We then showed that the DAF gene expression was up-regulated and the Dr + E. coli adhesion increased after the suppression of PI3K/Akt pathway in Ishikawa cells using inhibitor LY294002, and a plasmid which allowed the expression of PI3K/Akt regulatory protein PTEN. The down-regulation of PTEN protein using PTEN-specific siRNA activated the PI3K/Akt pathway, down-regulated the DAF, and decreased the adhesion of Dr + E. coli . We conclude that the PI3K/Akt pathway regulated the DAF expression in a nitric oxide independent manner.